A Historic-Contemporary Analysis of the Benefit-Sharing Agreement for South African Khoisan Rooibos Farmers - Steenkamp, William; Bisschoff, Christo (Journal of Economic Development, Environment and People, 2025)
The Rooibos Benefit-Sharing Agreement (BSA) represents ethical and legal failure, perpetuating historical injustices against the Khoisan people, while maintaining the racial and economic monopoly of the Rooibos industry. The agreement functions as a superficial compliance mechanism with the Nagoya Protocol, failing to ensure meaningful economic redress for Rooibos's Traditional Knowledge Holders (TKH) rather than serving as a restorative justice and fair-trade instrument. This article critically examines the contradictions between the BSA and international legal frameworks, including the Convention on Biological Diversity (CBD), the Nagoya Protocol, and access and benefit-sharing (ABS) principles. It argues that the agreement’s structure effectively excludes Khoisan Rooibos farmers from substantive participation in the Rooibos value chain, denying them control over their traditional knowledge and economic benefits. Despite being hailed as a landmark victory upon its implementation in 2019, the Rooibos BSA remains a mechanism of economic marginalization. Khoisan communities, whose traditional knowledge underpins the multi-billion-dollar Rooibos industry, receive a negligible share of industry profits, while historically privileged agribusinesses and multinational corporations retain dominance over production, processing, and international trade. This article critically analyses the agreement, the South African government's role in sustaining this inequitable framework, and its failure to enforce national and international legal obligations.